FINANCIAL EVALUATION OF LONG TERM INVESTMENTS: THE ROLE OF EXPLICIT PRODUCTION FUNCTIONS - Massot, Juan Miguel (European Scientific Journal, ESJ, 2014)
In the practice of evaluation of investment projects, the technique of discounted cash flows applies on income with functions such as logistic or neoclassical functions, which tend to be adverse on remote-time flows. However, these functions are not necessarily representative of the long term pathway of projects which are part of portfolios closely related to innovation or events with long-run externalities, such as education or environment. This paper concludes that production functions with human capital and externalities may cause distant flows to take values other than zero and produce relevant alterations of investment decisions.